FAT-FREE MASS AND SKELETAL MUSCLE MASS FIVE YEARS AFTER BARIATRIC SURGERY - Davidson, Lance E. (Obesity (Silver Spring), 2018)
OBJECTIVE: This study investigated changes in fat free mass (FFM) and skeletal muscle (SM) five years after surgery in participants from the Longitudinal Assessment of Bariatric Surgery-2 trial. METHODS: A 3-compartment model assessed FFM, and whole-body magnetic resonance imaging (MRI) quantified SM mass prior to surgery (T0), 1 year (T1), 2 years (T2), and 5 years (T5) postoperatively in 93 patients (85% female, 68% Caucasian, age 44.2 ± 11.6 yrs) who underwent gastric bypass (RYGB), sleeve gastrectomy (SLEEVE), or adjustable gastric band (BAND). Repeated-measures mixed models were used to analyze the data. RESULTS: Significant weight loss occurred across all surgical groups in females from T0 to T1. FFM loss from T0–T1 was greater after RYGB (mean±SE:−6.9±0.6 kg) than BAND (−3.5±1.4 kg; p<0.05). RYGB females continued to lose FFM (−3.3±0.7 kg; p<0.001) from T1 to T5. A subset of RYGB males and females with MRI-measured SM showed similar initial FFM loss while maintaining FFM and SM from T1 to T5. CONCLUSIONS: Between 1 and 5 years following common bariatric procedures, FFM and skeletal muscle are maintained or decrease minimally. The changes observed in FFM and muscle during the follow-up phase may be consistent with aging.